Alternative Centrifugal Pump Maintenance Systems Using Reliability Centered Maintenance (RCM II) and Life Cycle Cost (LCC) Methods in PDAM Surya Sembada Surabaya - Andita Rizki Ramadani; Joumil Aidil Saifuddin; Dira Ernawati (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The purpose of this study was to determine the pump failure factors, determine alternative pump maintenance intervals as an alternative maintenance policy, and minimize maintenance costs using the cost calculation method (LCC).  In this study, observations and interviews were carried out to obtain data related to the centrifugal pump machine. From the LCC (Life Cycle Cost) calculation above, it can be seen based on table 4.20, it is found that the smallest cost value is in year (n) = 5 with the number of mechanics (M) = 3 with the result of calculating a total cost of Rp. 1,515,507,735. So, it can be concluded that TC2 < TC1 with these results, the proposed method in this study is accepted. The maintenance interval for each centrifugal pump component is for the Impeller of 1,673 hours by selecting the Discard task, Shaft of 698 hours by selecting the scheduled restoration task, Bearing by 322 hours by selecting the scheduled restoration task, Coupling by 698 hours by selecting the scheduled restoration task, Mechanical seal for 2,131 hours with the selection of the scheduled discard task. The results of the calculation of the total cost of Rp. 1,515,507,735 as TC2 with a total company cost of IDR 1,600,000,000. So, it can be concluded that TC2 < TC1.